DAUN SIRSAK MENURUNKAN KADAR GULA DARAH PASIEN DIABETES MELLITUS - Putri Dafiani; Honesty Diana Morika (Jurnal Endurance, 2021)
Diabetes Mellitus (DM) is a chronic disease whose prevalence increases every year. Hyperglycemia is the cause of many complications. Various strategies continue to be pursued so that the level of morbidity and mortality is reduced. One of the efforts is using natural ingredients found in Indonesia to reduce hyperglycemia. The Soursop leaves (Annona muricata L) are one of the plants that are widely found in the Pesisir Selatan. It contains from flavonoids like tannins. Tannin contains antidiabetic. The purpose of this study was to study the effect of soursop leaves on reducing bloodglucose levels on diabetic patients. This study is a quasy experiment that uses DM patients in the working area of the Koto Baru Pesisir Selatan Public Health Center as a population. This research was conducted in June 2020. The sampling technique used was a simple random technique with a total sample of 16 people. The sample was divided into 2 groups, intervention and control. The intervention group consumed soursop leaf twice in day for 7 days. Blood glucose levels are taken before and after treatment. The data obtained were analyzed using independent t-test. The average results of blood sugar levels before giving soursop leaves were 322.62 mg / dL, after giving soursop leaves was 182.88 mg / dL. Blood sugar level in the control group before researching 308.63 mg / dL, after researching 297.62 mg / dL. The results of the study was value of p = 0.001. This means that there is a significant difference in blood glucose levels between the control group and the intervention group. Soursop leaves contain flavonoid compounds that are hypoglycemic so that they can help lower blood sugar levels. Health workers can educate DM patients to use soursop leaves as a supplement to DM medication so that DM patients' blood sugar levels can be controlled.